Makanan hantaran dalam perkahwinan Melayu Kelantan: adat dan interpretasi - Aishah@Eshah Haji Mohamed; Sulong Mohamad; Haziyah Hussain (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2010)
In the Kelantanese Malay weddings, it is a tradition for the bridegrooms and brides to exchange gifts. These gifts, known as hantarans include clothings, jewelaries and food. This article explores the hidden meanings and tradition of food hantarans in the Kelantanese Malay wedding ceremonies,with emphasis on behavior and symbolic aspects associated with food. The discussion here is based on a research in Kelantan that has been completed recently. The Kelantanese Malays have always included food as part of the hantarans, which are presented to either side in uneven numbers. These hantarans are placed neatly and decorated beautifully, befiting the socioeconomic status of the families of the brides, on pahars, containers with four legs, made from copper or bronze. These food hantarans have their own meaning and significance which are discussed in greater detail in this article